2018
DOI: 10.1080/08927022.2018.1455005
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical properties predicted by reactive force fields simulations for four common pure fluids at liquid and gaseous non-reactive conditions

Abstract: Four common pure fluids were chosen to elucidate the reliability of reactive force fields in estimating bulk properties of selected molecular systems: CH4, H2O, CO2 and H2. The pure fluids are not expected to undergo chemical reactions at the conditions chosen for these simulations. The 'combustion' ReaxFF was chosen as reactive force field. In the case of water, we also considered the 'aqueous' ReaxFF model. The results were compared to data obtained implementing popular classic force fields. In the gas phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Each model has advantages and disadvantages. The SPC/E model yields good results for structure and dynamics of bulk liquid water at ambient conditions and for static dielectric constant over a very wide range of temperatures and densities, but it underestimates water viscosity and fails to reproduce experimental vapor pressure, as well as other thermodynamic properties at critical and supercritical conditions . The SPC model is successful at reproducing the liquid–vapor coexistence curve and vapor pressure, , but it over-predicts the diffusion coefficient .…”
Section: Simulaton Methods and Algorithmsmentioning
confidence: 99%
“…Each model has advantages and disadvantages. The SPC/E model yields good results for structure and dynamics of bulk liquid water at ambient conditions and for static dielectric constant over a very wide range of temperatures and densities, but it underestimates water viscosity and fails to reproduce experimental vapor pressure, as well as other thermodynamic properties at critical and supercritical conditions . The SPC model is successful at reproducing the liquid–vapor coexistence curve and vapor pressure, , but it over-predicts the diffusion coefficient .…”
Section: Simulaton Methods and Algorithmsmentioning
confidence: 99%
“…[57][58][59] Recently, we found that the ReaxFF parameterisation can predict structural and transport properties of nonreactive pure fluids (CH4, CO2, H2O, and H2). 60 However, our results showed that the agreement with both classical simulations and experiments depends strongly on the fluid considered and on the thermodynamics conditions simulated.…”
Section: Co2 + 4h2 ↔ Ch4 + 2h2omentioning
confidence: 51%
“…ReaxFF parameters are obtained by fitting against training datasets containing quantum mechanical simulation results and experimental data. Accurate ReaxFF parameterizations have been applied to a wide range of reactive systems, including combustion processes, the shock-induced chemistry of high-energy materials, nanomaterials, catalysts, and also electrochemical phenomena. Recently, we found that the ReaxFF parameterization can predict structural and transport properties of nonreactive pure fluids (CH 4 , CO 2 , H 2 O, and H 2 ) . However, our results showed that the agreement with both classical simulations and experiments depends strongly on the fluid considered and on the thermodynamics conditions simulated.…”
Section: Introductionmentioning
confidence: 65%
“…The MSD plots are shown in Figure 9. It should be noted that simulation box size affects diffusion results estimated from MD simulations [57][58][59] because of finite-size effects due to the implementation of the periodic boundary conditions [60]. An analytical correction proportional to N −1/3 (N being number of molecules in the simulated box) has been proposed to account for such effects.…”
Section: Diffusion Of Confined Fluidsmentioning
confidence: 99%